Effect of Low-Density Lipoprotein Cholesterol Goal Achievement on Vascular Physiology Evaluated by Quantitative Flow Ratio in Patients Who Underwent Percutaneous Coronary Intervention - Chen, Long; Chen, Qin; Zhong, Jiaxin; Ye, Zhen; Ye, Mingfang; Yan, Yuanming; Chen, Lianglong; Luo, Yukun (Frontiers in Cardiovascular Medicine, 2021)
Purpose: The change in coronary physiology from lipid-lowing therapy（LLT）lacks an appropriate examination method. Quantitative flow ratio (QFR) is a novel angiography-based method allowing fast assessment of coronary physiology. This study sought to determine the impact of the low-density lipoprotein cholesterol (LDL-C) goal achievement on coronary physiology through QFR. Methods: Patients who underwent percutaneous coronary intervention (PCI) and one-year angiographic follow-up were screened and computed by QFR analysis. According to the LDL-C level at one-year follow-up, patients were divided into two groups:1) goal-achievement group (LDL-C< 1.8 mmol/l or reduction of ≥50%, n=146, lesion=165); 2) non-achievement group (n=286, lesion=331). All QFR data and major adverse cardiovascular and cerebrovascular events (MACCEs) at one year were compared between groups. Results: No differences between the groups were found in quantitative coronary angiography (QCA) data and QFR at post-PCI. At one-year follow-up, lower percentage diameter stenosis (DS %) and percentage area stenosis (AS %) were recorded in goal-achievement group (27.89±10.16 vs. 30.93±12.03, p=0.010, 36.57±16.12 vs. 41.68±17.39, p=0.003, respectively). Meanwhile, a higher QFR was found in goal-achieved patients (0.96±0.05 vs. 0.94±0.09, p=0.005). Furthermore, goal-achievement group had a lower incidence of physiological restenosis and MACCEs (2.1% vs. 8.4%, p=0.018, 5.4 % vs. 12.6 %, p=0.021, respectively). Conclusion: Evaluated by QFR, patients who achieved the LDL-C goal seem to have a better coronary physiological benefit. Meanwhile, this group of patients is presented a better clinical outcome.